Front Cover: An Organic Chemist's Guide to Mediated Laccase Oxidation (ChemBioChem 23/2022). (4th November 2022) - Obleser, Katharina; Kalaus, Hubert; Seidl, Bernhard; Kozich, Martin; Stanetty, Christian; Mihovilovic, Marko D.
Abstract : The mediator‐assisted laccase‐catalyzed oxidation of alcohols is a green alternative to established classical synthetic protocols. However, the consecutive interaction between oxygen, laccase, mediator and substrate comprises a complicated, multivariate system. This complexity can represent a substantial entry burden for the typical organic chemist, feeling both motivated and overwhelmed, just as the scientist in the cartoon. Herein, we present a detailed comparative study evaluating the most important parameters as a guidebook to using this powerful and attractive biocatalytic solution. More information can be found in the Research Article by C. Stanetty et al.